Effects of Plasma Sintering on the Post TIG Weld Joint of Fe-15Cr-25Ni Austenitic Stainless Steel - Parikin, Parikin; Dani, Mohammad; Dimyati, Arbi; Insani, Andon; Deswita, Deswita; Aziz, Ferhat; Mardiyanto, Mardiyanto; Mustofa, Salim; Purwanto, Setyo; Adhika, Damar Rastri; Syahbuddin, Syahbuddin; Huang, Ching An (Makara Journal of Technology, 2022)
Arc-plasma sintering (APS) for 5 s has been applied to the post tungsten inert gas (TIG) weld joint of Fe–15Cr–25Ni austenitic stainless steel (ASS). The treatment is intended to observe the effect of heat generated by plasma on micro-crystal structures around the fusion zone (FZ), especially internal stress relief in steel after being subjected to welding. The effect of stress relief in weld was measured using the neutron diffraction technique. ASS that is predominantly composed of Fe, Cr, and Ni elements, with contents of 57%, 15%, and 25%wt. respectively, was cut into two parts. Both parts were then welded with TIG without filler with a current and voltage of 60 A and 50 V, respectively. After APS for 5 s, the sample was characterized and analyzed using high-resolution powder neutron diffractometer at a high-temperature laboratory facility. The results show that the tensile residual stress decreased with the APS heat input. The residual stresses significantly decreased from 82.40 MPa to 1.21 MPa in the FZ and continued almost evenly from 65.92 MPa to 1.24 MPa in the heat-affected zone (HAZ). The residual stress is a tensile stress that can reduce the mechanical strength of materials. This condition is also applicable to applied loads. A microstructure gives a confirmation that the C element migrates from the FZ to HAZ. The content was very high in dark traces. The C element reacts to Cr and O to form chromium carbide (Cr23C6) and chromium carbonyl (CrC6O6), respectively. It rapidly migrates among its grain boundaries. It may also weaken materials and probably initiate intergranular cracks.